Achieving Efficient NIR-II Type-I Photosensitizers for Photodynamic/Photothermal Therapy upon Regulating Chalcogen Elements - Wen, Kaikai (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.